Pengendalian Kualitas Produk Sari Buah Markisa Dengan Label “Luxury Seeowrens” Melalui Analisis Kadar Vitamin C, Kalsium Dan Aktivitas Antioksidan Untuk Mitra Markisa Manis Mampang, Pancoran Mas,Kota Depok, Jawa Barat - Hotlina Nainggolan; Dina Melia Oktavilantika; Harits Atika Ariyanta; Dyah Mieta Setyawati (PT. ALHAFI BERKAH INDONESIA, 2023)
Community Service Activity Program, Gunadarma University Pharmacy Study Program in collaboration with Gunadarma University LPM, seeks to control the quality of passion fruit juice drink products with the label